Answer:
Fourth option is the correct one.
Step-by-step explanation:
Given:
[tex]A = \left[\begin{array}{ccc}1&2\\3&4\end{array}\right][/tex]
Lets Assume
[tex]B = \left[\begin{array}{ccc}4&0\\0&1\end{array}\right][/tex]
Now,
if we multiply both in sequence AB, we get
[tex]AB = \left[\begin{array}{ccc}1&2\\3&4\end{array}\right] \left[\begin{array}{ccc}4&0\\0&1\end{array}\right][/tex]
[tex]AB = \left[\begin{array}{ccc}1.4+2.0&1.0+2.1\\3.4+4.0&3.0+4.1\end{array}\right][/tex]
[tex]AB = \left[\begin{array}{ccc}4&2\\12&4\end{array}\right][/tex]
Now if we multiply both in sequence BA, we get
[tex]BA = \left[\begin{array}{ccc}4&0\\0&1\end{array}\right] \left[\begin{array}{ccc}1&2\\3&4\end{array}\right][/tex]
= [tex]\left[\begin{array}{ccc}4.1+0.3&4.2+0.4\\0.1+1.3&0.2+1.4\end{array}\right][/tex]
[tex]BA = \left[\begin{array}{ccc}4&8\\3&4\end{array}\right][/tex]
Hence AB ≠ BA
Now according to equation,
(A+B)² = A² + B² + AB + BA = A² + B² + 2AB only when AB = BA which is not the case as seen in example above